PENGARUH KOTORAN LARVA KUMBANG TANDUK (Oryctes rhinocerosL) TERHADAP KEPADATAN DAN KERAGAMAN MAKROFAUNA TANAH DI PIRINGAN TANAMAN KELAPA SAWIT (Elaeis guinensis Jacq) - Fidiadi, Muhammad; Wardati, Wardati; Salbiah, Desita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Palm oil (Elaeis guineensis Jacq) is an important industrial plant for edible oil, industrial oil,and others. The efforts for getting maximal yield, palm oil companies and small holder farmers use chemical material that affected on reducing of environment quality, such as soil biological properties. The research aim to determine effect of the horn beetle larvae feces (Oryctes rhinoceros L) on density and diversity of soil macrofauna in dish of palm oil plant. The research was conducted at PTPN V Kebun Sei Galuh, Kampar Regency and the Soil Science Laboratory, Agriculture Faculty, Riau University. There were 4 dosage treatments of the horn beetle larvae feces, that are 0, 5, 10, and 15 kg/plant and repeated 4 times. The result showed that the horn beetle larvae feces increased the density and diversity of soil macrofauna. At a dosage of 15 kg/plant showed the highest population density on each month, and the treatment of horn beetle larvae feces at different dosage showed the middle diversity on the each month. Keywords: Palm oil, thehorn beetle larvae,macrofauna,density, diversity